Itinerarios profesionales de los estudiantes de ciencias de la actividad física y del deporte - Rodríguez Romo, Gabriel; Rivero Herráiz, Antonio; Montil Jiménez, Marta Matilde; Garrido Muñoz, María (KRONOS, 2007)
The purpose of this study was to evaluate which were the preferred areas of professional specialisation among students from Physical Activity and Sport Sciences School from Universidad Europea de Madrid. Sample was 805 (sampling error + 1,8% and confi dent interval of 95,5%), who completed a questionnaire during the period of time 2002-2006. The results of the study suggested the existence of differences among the areas of professional specialisation selected by students (physical education, 35.1%; physical activity and health, 24.1%; fi tness training, 14.9%, sport management, 13.8%; and sport training, 12.1%). Moreover, the results obtained also indicated the existence of signifi cant differences according to gender [c2(4)=35.14; p<.001], age [c2(8)=45.21; p<.001], access to the School [c2(4)=15.22; p<.01] and student year [c2(8)=65.76; p<.001].